Assessment of fecal steroid and thyroid hormone metabolites in eastern North Pacific gray whales. Issue 1 (7th December 2020) - Lemos, Leila S; Olsen, Amy; Smith, Angela; Chandler, Todd E; Larson, Shawn; Hunt, Kathleen; Torres, Leigh G
Abstract : An improved understanding of baleen whale hormone physiology is required to manage populations and reduce anthropogenic impacts. Gray whale fecal samples were assessed, and hormone metabolites quantified, which varied by demographic units and years. Two case studies are presented providing reference points for physiologically stressed individuals and adult breeding males. Abstract: Baleen whale fecal samples have high potential for endocrine monitoring, which can be used as a non-invasive tool to identify the physiological response to disturbance events and describe population health and vital rates. In this study, we used commercial enzyme-linked immunosorbent assays to validate and quantify fecal steroid (progestins, androgens and glucocorticoids) and thyroid hormone metabolite concentrations in eastern North Pacific gray whales ( Eschrichtius robustus ) along the Oregon coast, USA, from May to October of 2016–2018. Higher mean progestin metabolite concentrations were observed in postweaning females, followed by pregnant females. Mean androgen, glucocorticoid and thyroid metabolites were higher in mature males. Progestin, glucocorticoids and thyroid fecal metabolites varied significantly by year, with positive correlations between progestin and androgen, and between glucocorticoid and thyroid metabolites. We also present two case studies of a documented injured whale and a mature male displaying reproductive competitive behavior, which provide reference points for physiologically stressed individuals and adult breeding males, respectively. Our methods and findings advance the knowledge of baleen whale physiology, can help guide future research on whale physiology and can inform population management and conservation efforts regarding minimizing the impact of anthropogenic stressors on whales.